KEPASTIAN HUKUM ATAS PEMINJAMAN PERUSAHAAN OLEH PIHAK KETIGA YANG DIBUAT DENGAN AKTA NOTARIS TERKAIT DENGAN PENGADAAN BARANG DAN JASA - Jesslyn Kisea Tinambunan (LPPM STIH Awang Long, 2023)
In the implementation of procurement of goods/services, sometimes there is abuse by contractors in gaining profits without fulfilling their obligations by lending their company name to work on the project to a third party in exchange for a project fee. The winning bidder and the third party make a new agreement regarding the project to be carried out. In this research, the formulation of the problem is how is legal certainty regarding company loans by third parties made by notarial deed related to the procurement of goods and services? This research method is included in the form of normative juridical research. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis was carried out using qualitative juridical data analysis methods. The research results show that legal certainty regarding company loans by third parties made by notarial deeds related to the procurement of goods and services is not fulfilled. This is because it does not fulfill the provisions in Article 1320 of the Civil Code, especially the objective requirements which consist of certain things that are agreed upon and lawful causes. Therefore, this has implications for the cancellation of Deed Number 61 dated 27 July 2011 made by Notary Fitri Yuliana, SH, regarding company loans by third parties for the procurement of goods and services. Apart from that, there are other legal implications for the parties, namely for parties who default, they will be subject to administrative sanctions, be sued for compensation and/or be criminally reported. The party who suffers losses due to default can terminate the contract and the party who defaults is obliged to return the benefits and achievements. If this is not fulfilled by the party in default, then the aggrieved party can take legal action through a civil lawsuit to the district court.